2021
DOI: 10.1111/gwao.12764
|View full text |Cite
|
Sign up to set email alerts
|

“A trade of one's own”: The role of social and cultural capital in the success of women in male‐dominated occupations

Abstract: The skilled trades are highly gender segregated occupations. Unsurprisingly, research about women in this male-dominated sector focuses on the various barriers to inclusion. In contrast, this article identifies factors that have contributed to women's successes. Drawing on in-depth interviews with tradeswomen, we found that the success factors for women in the skilled trades were aligned with social and cultural capital. Findings also indicate that women's success is driven by their individual attributes and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(75 reference statements)
3
17
0
Order By: Relevance
“…Scholars have argued for a variety of ways to address gendered and racial inequalities within the trades: more inclusive recruitment strategies (Jenkins et al 2019; Simon and Clarke 2016), additional emphasis on mentoring (Galea et al 2015; Jenkins et al 2019; MacIsaac and Domene 2014; Simon and Clarke 2016; Taylor et al 2015; Wright 2016), and addressing the formal rules of trades organizations to address institutionalized inequalities (Galea et al 2015). Advocates for a diverse construction trades workforce echo these calls and also suggest additional efforts, such as respectful workplace trainings and workforce participation goals (Bridges et al 2019; Haines et al 2020; Hegewisch et al 2014; Hegewisch and O’Farrell 2014, 2015; Moir et al 2011; National Women’s Law Center 2014; Policy Group on Tradeswomen’s Issues 2016). The findings of this study suggest that while retention can be improved by providing supportive services to individual apprentices, larger structural changes are also needed to support a diverse construction workforce.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Scholars have argued for a variety of ways to address gendered and racial inequalities within the trades: more inclusive recruitment strategies (Jenkins et al 2019; Simon and Clarke 2016), additional emphasis on mentoring (Galea et al 2015; Jenkins et al 2019; MacIsaac and Domene 2014; Simon and Clarke 2016; Taylor et al 2015; Wright 2016), and addressing the formal rules of trades organizations to address institutionalized inequalities (Galea et al 2015). Advocates for a diverse construction trades workforce echo these calls and also suggest additional efforts, such as respectful workplace trainings and workforce participation goals (Bridges et al 2019; Haines et al 2020; Hegewisch et al 2014; Hegewisch and O’Farrell 2014, 2015; Moir et al 2011; National Women’s Law Center 2014; Policy Group on Tradeswomen’s Issues 2016). The findings of this study suggest that while retention can be improved by providing supportive services to individual apprentices, larger structural changes are also needed to support a diverse construction workforce.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Research into the experiences of women in male-dominated trade occupations (Bridges et al, 2019; Galea et al, 2020) has found that women experience inequality regimes prior to entry through poor access to informal networks and information, being excluded from skills-based recruitment activities and other recruitment processes within the industry. Once past the recruitment hurdle, tradeswomen find organisational processes such as inflexible work hours, lack of access to leave and limited career paths that restrict their opportunities for development and growth.…”
Section: Organisational Inequality Regimesmentioning
confidence: 99%
“…Since the 1980s in Australia, industry, government and the education sector have sought to increase number of women in male-dominated skilled trade occupations to no avail. A range of organisational practices and processes, including informal recruitment processes, gendered workplace policies and a lack of mentors, role models and female leadership, have been identified as key barriers to women’s employment in the skilled trades (Bridges et al, 2019, 2020; Fielden et al, 2000; Galea et al, 2020; MacIsaac and Domene, 2014; Smith, 2013; Wright, 2013, 2016). Furthermore, individualised mechanisms of exclusion and the concept of ‘borderwork’, which includes the use of gender stereotypes, sexual harassment, masculine culture, discrimination and violence, have also been flagged as significant barriers to women’s ongoing employment (Denissen, 2010a, 2010b; Denissen and Saguy, 2014; Fielden et al, 2000; Smith, 2013; Wagner, 2014; Wright, 2013, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations